2021
DOI: 10.1111/jfpp.15432
|View full text |Cite
|
Sign up to set email alerts
|

Application of electronic nose with chemometrics methods to the detection of juices fraud

Abstract: Prevention of food adulteration has been a controversial topic in the last decade, and various intervention systems have been developed to prevent counterfeit products from entering the supply chain.Therefore, reliable analytical tools are needed to validate food products (Spink et al., 2017).Consumers and the beverage industries have considered monitoring the quality and freshness of fruit juices. Receiving significant attention from the consumers due to the nutritional and sensory properties. Quality has bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…The results of the AOCS methods confirm the initial classification obtained in the score plot. Rasekh and Karami (2021a) reported similar results for predicting fruit fraud.…”
Section: Data Exploratory Analysismentioning
confidence: 57%
“…The results of the AOCS methods confirm the initial classification obtained in the score plot. Rasekh and Karami (2021a) reported similar results for predicting fruit fraud.…”
Section: Data Exploratory Analysismentioning
confidence: 57%
“…Rasekh and Karami [ 26 , 27 ] reported similar results for predicting fruit juice fraud. In addition, the results obtained in this study were far higher than the values reported by Ayari et al [ 38 ] for the detection of oxidation in animal and herbal oils.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, 9 Metal Oxide Semiconductor (MOS) sensors with low power consumption are used in this apparatus. The sensor specifications are listed in Table 2 [ 22 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the designed electronic nose system used a combination of 9 metal oxide semiconductor sensors with MQ and TGS trademarks . [14] Table 1. The used sensors in electronic nose The computer stored the output signal data of the sensors during the measurement period, as one data per second.…”
Section: Electronic Nose Systemmentioning
confidence: 99%